Inclusive practices and policies in language teacher education courses - Medrada, Betânia Passos; Mello, Dilma; Tonelli, Juliana Reichert Assunção (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2019)
The current legislation regulating basic education in Brazil (Brasil, 2013) and the inclusion of students with speciﬁc educational needs in regular schools (Brasil, 2015) warrant some reﬂections on the discourses and actions in the ﬁeld of language teacher education. We have observed that the implementation of inclusive practices in Brazilian schools has been a time-consuming process as it implies not only changes in public policies, but also — and maybe primarily — several kinds of transformation in educational contexts. Considering the broad spectrum of students’speciﬁc educational needs, given the innumerable types of pathologies and their nuances, as well as keeping in mind the assumption that teachers can only create some space for inclusive practices in the classroom if their education is based on critical, autonomous, and informed thinking (Celani, 2010), we consider it to be essential to explore the language teacher education landscape. It seems important to highlight that our understanding of inclusive practices is related to the process of identifying and reﬂecting on what social-affective, ethical, and pedagogical changes are needed, not only providing accessibility and architectural changes as is usually done. However, this perspective still requires some debate on the language teacher education courses in our country. In this paper, we discuss the inclusive practices, programs, and studies carried out at three Brazilian universities: Federal University of Paraíba, State University of Londrina, and Federal University of Uberlândia. Our aim is to analyze the way inclusive matters have been or can be incorporated into the pedagogical project, the teacher practicum, and/or the individual projects of teacher educators in the institutions mentioned in this paper.